Gender, Intraparty Competition, and the Substantive Focus of Parliamentary Questions in South Africa - Espírito-Santo, Ana (2024)
Extant research suggests that women ask more parliamentary questions (PQs) on soft policy domains while their male peers focus on hard domains, which are arguably more relevant. This study contributes to this body of research by examining how electoral incentives shape intraparty politics, and specifically the substantive focus of PQs. It argues that women’s focus on soft policy domains is not constant, with variations found in situations where intraparty competition is high. Female MPs will have fewer incentives to focus on soft policy domains if they are electorally vulnerable and as elections draw closer. The mechanism is clear: Women face strong bias in parliament, which means they need to work harder to stand on an equal footing with their male counterparts. As a result, rather than shying away from competition, they will try to maximize their career prospects by shifting their attention to (hard) policy domains that are considered more important to both parties and voters. These claims are tested in the case of South Africa, drawing upon a novel dataset of PQs from 2006 to 2023. South Africa is an interesting case study as it is one of the most feminized parliaments in Africa and has strong electoral incentives for intraparty competition. The findings confirm most theoretical expectations and clarify the electoral and gender-related predispositions that drive the substantive focus of questions.